If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = s + -1p Reorder the terms: 16 = -1p + s Solving 16 = -1p + s Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'p' to each side of the equation. 16 + p = -1p + p + s Combine like terms: -1p + p = 0 16 + p = 0 + s 16 + p = s Add '-16' to each side of the equation. 16 + -16 + p = -16 + s Combine like terms: 16 + -16 = 0 0 + p = -16 + s p = -16 + s Simplifying p = -16 + s
| 12v^2+12v-15=0 | | 72-4.9t^2=8t | | 4x-4=-48 | | 3/10+7/10 | | 0-600*2-600*2+X*2-0.2X*4=0 | | a^2-a-8=0 | | 7/10+1/5 | | 4x+7-3x=15 | | -4n+2+3n=8-n+6 | | 5/12+5/12 | | 2x-1/2(3x-2)=7/4-x | | 0=18x^2 | | X-22=15 | | -6-8=9x+7-8x | | -x^2-23x-60=0 | | 17/19+1/19 | | w/4=13 | | -3+21=m-8 | | x*2-0.2x*4x-2400=0 | | 4x-8=5x-2(x+2) | | f(1.8)=2x*x-16x+63 | | x/x+4 | | 1/x+4 | | x-4/x-16 | | f(1.8)=2x*2x-16x+63 | | y/8=17 | | (x-9)(2x^2+x-3)= | | 5/12+1/2 | | 9y-12y=-10-14 | | .24y-4=.14y+2-.7y | | 1/15+3/5 | | 2/5+9/20 |